POLA HUBUNGAN RELASIONAL PADA PASANGAN SEJENIS: (SEBUAH PENELITIAN EMPIRIS DENGAN PERSPEKTIF TEORI DIALEKTIKA RELASIONAL) - Moch Nasrulloh (Jurnal Dakwah Tabligh, 2019)
Abstract This paper try to describe about the system of relational connection in the guy couple. This connection analyzed by it’s theory to get a conclusion. Actually, in the relational connection, there are the dialectic of centriphetal and centrifugal in which centriphetal energy pull inside to the center of connection. It’s diffirent from centrifugal energy that pull outside from the center of connection. Both of that energy dominate connection one to the other. Because of that, the principle duty of each couple is harmonize both of the diffirent energy for balance, but not make disappear centrifugal energy. Certainly, destructive energy of centrifugal is not avoided. That energy is not be passed away, but it’s has to be compromised and communicated well, so it’s relation can be composed powerfully.  Key word : dialectics, dialogue, centripetal, centrifugal, relational.